The genome sequence of the bramble shoot moth, Notocelia uddmanniana (Linnaeus, 1758) - Boyes, D; Holland, PWH (F1000 Research Ltd, 2021)
We present a genome assembly from an individual male Notocelia uddmanniana (the bramble shoot moth; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence is 794 megabases in span. The majority of the assembly, 99.96%, is scaffolded into 28 chromosomal pseudomolecules, with the Z sex chromosome assembled.